Leadership Communication and Organizational Culture: A Communicative Constitution of Organizations Perspective - Sumarlan, Iman (Fast in Social Sciences, 2025)
This study explores the role of leadership communication in shaping organizational culture through the lens of the Communicative Constitution of Organizations (CCO) theory. While previous studies often treat leadership and culture as separate organizational elements, this research positions communication as the core mechanism that constitutes both. The objective of this study is to examine how leaders’ communicative practices—ranging from narrative construction to discursive interactions—actively create, maintain, and transform organizational culture. Employing a qualitative case study method, data were collected through in-depth interviews, participant observation, and document analysis within a values-based organization. Thematic analysis was conducted to identify communicative patterns that reflect the enactment of leadership and the constitution of cultural values. The findings indicate that leadership communication does not merely reflect organizational culture but functions as its constitutive force, particularly through symbolic narratives, strategic language, and everyday interactions that reinforce shared meanings. Furthermore, the study reveals how organizational members co-author these cultural narratives through engagement with leadership discourse. The conclusion emphasizes the importance of viewing leadership as a communicative process that continuously shapes organizational reality. This study contributes to the development of communicative organizational theory and offers practical implications for leaders aiming to build strong, value-driven organizational cultures through intentional and inclusive communication